1994
DOI: 10.1002/jcc.540150502
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the role of the solvent on the reaction mechanisms: One‐step versus two‐step ketene–imine cycloaddition

Abstract: The effect of correlation energy, basis set size, zero-point energy (ZPE) correction, and solvation on the reaction mechanism of the ketene-imine cycloaddition reaction has been investigated. The electrostatic solvent effect was studied with a self-consistent reaction field method in which the solvation energy is obtained using a multipole expansion of the molecular charge distribution. The ab initio results have been analyzed by means of a theoretical method based on the expansion of the MOs of the supermolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 47 publications
4
26
0
Order By: Relevance
“…The free energy surface in solution is directly evaluated and the transition state may be located on that surface without any ap-proximation other than that related to the solvent model. The self-consistent reaction field ͑SCRF͒ model developed in our group 30 has been widely employed to study equilibrium solvent effects on chemical reactions 31 and has been shown to be particularly useful to analyse reaction mechanisms and free energy surfaces. 32 Since for the process considered here, the reaction coordinate does not have a trivial definition, we have decided to employ the last option.…”
Section: A Choice Of Initial Conditionsmentioning
confidence: 99%
“…The free energy surface in solution is directly evaluated and the transition state may be located on that surface without any ap-proximation other than that related to the solvent model. The self-consistent reaction field ͑SCRF͒ model developed in our group 30 has been widely employed to study equilibrium solvent effects on chemical reactions 31 and has been shown to be particularly useful to analyse reaction mechanisms and free energy surfaces. 32 Since for the process considered here, the reaction coordinate does not have a trivial definition, we have decided to employ the last option.…”
Section: A Choice Of Initial Conditionsmentioning
confidence: 99%
“…The conformational preferences of I have been investigated at both semiempirical [11] and ab initio [12] levels, in the latter using the medium size 6-3 IG basis set. On the other hand, the mechanism of the ketene-imine cycloaddition reaction, which is one of the methods leading to the formation of ~-lactams, has been investigated using high-level quantum mechanical calculations [13][14][15][16][17]. Furthermore, the effect of solvation on the mechanism of this reaction has been examined using a self-consistent reaction-field (SCRF) procedure [17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the mechanism of the ketene-imine cycloaddition reaction, which is one of the methods leading to the formation of ~-lactams, has been investigated using high-level quantum mechanical calculations [13][14][15][16][17]. Furthermore, the effect of solvation on the mechanism of this reaction has been examined using a self-consistent reaction-field (SCRF) procedure [17]. Nevertheless, very little is known about the conformational and electrostatic properties of 2-azetidinone derivatives monosubstituted at C4.…”
Section: Introductionmentioning
confidence: 99%
“…Based on ap reviously reportedt heory that this cycloaddition reaction is not concerted,b ut rather at wo-step process (depending on the solvent), [33] it is conceivable that as lightly more-electron-rich aryl group on the ketimine nitrogen atom would perform better.I ndeed, this proposal was found to be true in the synthesis of racemic b-lactam 19 b (73 %y ield), in which the N-aryl group contained am ethoxy substituent. Moreover, nitrile-substituted b-lactam 19 c was isolated in a low (18 %) yield;h owever, it was still not certainw hether an electronic argument could be applied to our two-step process, given the yield of fluorinated b-lactam 19 d (86 %).…”
Section: Resultsmentioning
confidence: 99%